Pelatihan Pembuatan Pestisida Alami Daun Sirih sebagai Upaya Pengendalian Hama di Lingkungan Masyarakat Dusun Paya Pinang, Stabat Lama Barat, Kec. Wampu, Kab. Langkat - Raja Siti Aisyah Siti Aisyah; Syaprina Anggriani; Zahwa Adiesty; Destri Br Maha (EduInovasi: Journal of Basic Educational Studies, 2023)
As a global biodiversity conservation area which is a habitat for many protected animals and plants, conditions and safety need to be considered. It is necessary to pay attention to threats from various factors, especially factors from the environment itself, namely pests. Pestidia play an important role in pest control. The effect of herbal pesticides from the leaves of the tree (piper betle L). on pest mortality by shortening the life cycle of pests in the larval phase, the level of plant damage, plant weight and nutrition and effective doses of betel leaf pesticides as pest control. The highest pest mortality was found at a dose of 10% betel leaf pesticide, namely 64%. Betel leaf pesticides also cause shortening of the pest life cycle in the larval phase with the highest percentage of pupae at a treatment dose of 2.5%, namely 36%. Spraying betel leaf pesticides has an effect on the level of damage to plants. Keywords: biodiversity, natural pesticides